Innowacyjność europejskiej przestrzeni regionalnej - ocena zmian w czasie - Strahl, Danuta; Markowska, Małgorzata (Innovation of European Regional Space - Assessment of Changes in Time, 2008)
The article presents the results of empirical studies conducted in regions of the European Union countries at NUTS 2 level with reference to attributes illustrating innovation processes. The output of EU statistics was used for the assessment of regional innovation, which allowed for including the following characteristics in the description of innovation processes occurring in the European regional space: the share of employed university graduates in the total number of workers in the region, human resources in science and technology as the percentage of professionally active employees, the share of population aged 25-64 participating in continuing education in the region, the share of the employed in high and mid-tech industry in the total labour force number in the region, the share of the employed in services "knowledge intensive services" in the total labour force in the region, patents registered in a given year in EPO per million of labour force in the region. The synthetic indicator of regional innovation (SIRI) was used for the assessment of changes occurring in time in the European regional space. It was calculated for five time points of the conducted observations. The research allowed for distinguishing regions characterized by the strongest position, with reference to regional innovation level, as well as the regions presenting the lowest level of the studied phenomenon. The position of Polish regions representing NUTS 2 level was also defined at the background of the European regional space in five points analyzed in time, as well as the position changes occurring in the order of regions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 33-43